1991
DOI: 10.1177/026765919100600307
|View full text |Cite
|
Sign up to set email alerts
|

Portable cardiopulmonary bypass for heart-lung donor transplants

Abstract: In 1985 a portable cardiopulmonary bypass machine was devised in order that heart-lung donors from hospitals that were some distance away from our own institution could be procured. The distance of these hospitals ranged from the far north of Scotland to the Greek city of Athens. This paper will show how the portable bypass machine was developed and how it is used for the procurement of donor organs. As an offshoot of this, the device has been used for two emergency bypass procedures at noncardiac units whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…63,64 Similar techniques have been used with success in clinical transplantation involving other organs, with promising results. [65][66][67][68][69] Experimental studies on liver have shown that extracorporeal perfusion has the ability to 'recondition' the marginal liver grafts that have undergone warm ischemic injury during NHBD procurement, and in those with steatosis. 64,[70][71][72][73] Selectively applied, these organ preservation and salvage techniques carry promise of a significant supply of grafts rehabilitated in vitro.…”
Section: Machine Perfusion Of Organs and Organ 'Reconditioning'mentioning
confidence: 99%
See 1 more Smart Citation
“…63,64 Similar techniques have been used with success in clinical transplantation involving other organs, with promising results. [65][66][67][68][69] Experimental studies on liver have shown that extracorporeal perfusion has the ability to 'recondition' the marginal liver grafts that have undergone warm ischemic injury during NHBD procurement, and in those with steatosis. 64,[70][71][72][73] Selectively applied, these organ preservation and salvage techniques carry promise of a significant supply of grafts rehabilitated in vitro.…”
Section: Machine Perfusion Of Organs and Organ 'Reconditioning'mentioning
confidence: 99%
“…The key benefits are a reduction in preservation injury and improved ability to withstand prolonged ischemia with preserved hepatocellular function 63,64 . Similar techniques have been used with success in clinical transplantation involving other organs, with promising results 65–69 . Experimental studies on liver have shown that extracorporeal perfusion has the ability to ‘recondition’ the marginal liver grafts that have undergone warm ischemic injury during NHBD procurement, and in those with steatosis 64,70–73 .…”
Section: Future Of Liver Transplantationmentioning
confidence: 99%